Effect of Si content on mechanical properties of Nb-Si based alloys with Nbss/Nb5Si3 structure - 郑鹏 沙江波 刘东明 宫声凯 除惠彬 (Transactions of Nonferrous Metals Society of China, 2006)
In Nb-Si based alloys with a two-phase Nbss/intermetallic Nb5Si3 structure, the Nb5Si3 provides high-temperature strength, while the bib solid-solution phase, Nbss, contributes to room-temperature ductility and toughness. The results show that in Nb-15W-10Hf-xSi alloys （x = 0.5, 5 and 18, mole fraction, %）, the volume fraction of the Nb5Si3 is 0 for the 0.5% Si sample, 15% for the 5% Si sample and the 50% for 18% Si sample. With increasing Si content, i.e., the Nb5Si3 fraction, the high-temperature strength is improved considerably, but room-temperature ductility and toughness are degraded. For the sample Nb-15W-10Hf-18Si with 50% Nb5Si3, the compressive strength at 1 500 ℃ and the room-temperature fracture toughness are 500 MPa and 6.8 MPa·m^1/2, respectively, those for the Nb5Si3 free sample, Nb-15W-10Hf-0.5Si, are 190 MPa and 13.6 MPa·m^1/2.